Estudo paramétrico e análise de configurações alternativas para feixes de molas objetivando a redução de massa - Leonardo do Carmo Lelis Dias (2022)
The purpose of this work is to conduct a parametric study on leaf springs and propose alternative p for reducing the component's mass, using alternative materials to steel and proposals for new geometries. The component was selected as the study object because it is the main item of a vehicle suspension, and it has a high optimization potential. In order to understand the parameters with the greatest influence and evaluate the leaf springs, static and modal analyses were conducted using the Ansys Workbench®️ software. Based on the analyses results, two alternative configurations for leaf springs were proposed: the first parabolic, in which the leaves have a thickness variation; and the second, a hybrid set, combining steel and epoxy fiberglass. In the first case, improvements in the mechanical behavior of the component were observed, however, a small increase in mass was also noted when compared to a leaf spring obtained analytically. However, when compared to the commercial component, a weight reduction of 5.9 kg was seen. For the proposed hybrid leaf spring, the mass minimization achieved was more effective, being approximately 42%, however, it was verified that there was a loss in terms of stress and deflection, being 20.91% and 23.93% respectively, compared to the conventional analytical leaf spring. Since the weight reduction is greater than the losses, the results were beneficial for the proposed solution. Alternative configurations for monoleaf springs were also proposed, these being: hybrid, with thickness variation, and with width variation. These proposals have a better mechanical response than the conventional steel system, reaching an expressive weight reduction. Due to the positive results achieved with the hybrid configuration in leaf springs, the concept was applied to the monoleaf with varying geometry, increasing the gains obtained. Comparing the hybrid monoleaf with thickness variation to the analytically calculated leaf spring, a 61.47% reduction in the component's mass is observed, being the best result obtained throughout the work. To validate these results, the reduction in fuel consumption was evaluated, considering the average consumption of the selected vehicle category. A maximum optimization of 0.151 km/l and a minimum of 0.068 km/l was reached. Based on data from the literature, it was also shown that these gains have positive impacts on reducing emission indices.